Flow cytometric fluorescence pulse width analysis of etoposide-induced nuclear enlargement in HCT116 cells - Kang, Kyungsu; Lee, Saet Byoul; Yoo, Ji-Hye; Nho, Chu Won (SPRINGER, 2010)
Fluorescence pulse width can provide size information on the fluorescence-emitting particle, such as the nuclei of propidium iodide-stained cells. To analyze nuclear size in the present study, rather than perform the simple doublet discrimination approach usually employed in flow cytometric DNA content analyses, we assessed the pulse width of the propidium iodide fluorescence signal. The anti-cancer drug etoposide is reportedly cytostatic, can induce a strong G2/M arrest, and results in nuclear enlargement. Based on these characteristics, we used etoposide-treated HCT116 cells as our experimental model system. The fluorescence pulse widths (FL2-W) of etoposide-treated (10 mu M, 48 h) cells were distributed at higher positions than those of vehicle control, so the peak FL2-W value of etoposide-treated cells appeared at 400 while those of vehicle control cells appeared at 200 and 270. These results were consistent with our microscopic observations. This etoposide-induced increase in FL2-W was more apparent in G2/M phase than other cell cycle phases, suggesting that etoposide-induced nuclear enlargement preferentially occurred in G2/M phase cells rather than in G0/G1 or S phase cells.
Keywords: APOPTOSIS; PATHWAY; ARREST; DEATH; CYCLE